ANTIBIOTIC RESISTANCE OF KLEBSIELLA PNEUMONIAE TO CEPHALOSPORINS - E. V. Anganova (Acta Biomedica Scientifica, 2017)
Bacteria Klebsiella pneumoniae is one of the most common and dangerous pathogens of human infectious diseases. The research of K. pneumoniae resistance to ß-lactam antibiotics (cephalosporins), which are widely used in anti-infective therapy, is very relevant. The aims of the work is to study K. pneumoniae resistance to cephalosporins. Fifty strains of K. pneumoniae isolated from patients (sputum, lavage liquid, blood) of Irkutsk Regional Clinical Hospital and sectional material in 2015 were examined. Resistance to four antibiotics (cefotaxime, ceftriaxone, ceftazidime, cefepime) was determined by disco-diffusion method. 56.0-62.0 % of K. pneumoniae strains were resistant to drugs of 111 generation cephalosporins; 58.0 % - to drug of 1Vgeneration (cefepime). Klebsiella strains showed the highest resistance to ceftazidime (resistance - 62.0 %; intermediate - 20.0 %). The spectrum of resistance to all four antibiotics was revealed in 52.0 % of strains, cross-resistance - in 64.0 %. The resistance of K. pneumoniae from the sectional material was higher than resistance of Klebsiella isolated from the organs and tissues of the patients. Klebsiella isolated from the lavage fluid more often (p < 0.05) showed resistance to cephalosporins compared to strains isolated from sputum. The research brought us to the conclusion that Klebsiella pneumoniae strains were characterized by a significant level of resistance to ß-lactam antibiotics (cephalosporins).